Tree size and climatic water deficit control root to shoot ratio in individual trees globally - Ledo, A.; Paul, K.I.; Burslem, D.F.R.P.; Ewel, J.J.; Barton, C.; Battaglia, M.; Brooksbank, K.; Carter, J.; Eid, T.H.; England, J.R.; Fitzgerald, A.; Jonson, J.; et al. (WILEY, 2017)
Plants acquire carbon from the atmosphere and allocate it among different organs in response to environmental and developmental constraints (Hodge, 2004; Poorter et al ., 2012). One classic example of differential allocation is the relative investment into aboveground vs belowground organs, captured by the root : shoot ratio (R : S ; Cairns et al ., 1997). Optimal partitioning theory suggests that plants allocate more resources to the organ that acquires the most limiting resource (Reynolds & Thornley, 1982; Johnson & Thornley, 1987). Accordingly, plants would allocate more carbon to roots if the limiting resources are belowground, that is water and nutrients, and would allocate more carbon aboveground when the limiting resource is light or CO2. This theory has been supported by recent research showing that the R : S of an individual plant is modulated by environmental factors (Poorter et al ., 2012; Fatichi et al ., 2014). However, understanding the mechanisms underpinning plant allocation and its response to environmental factors is an active field of research (Delpierre et al ., 2016; Paul et al ., 2016), and it is likely that plant size and species composition have an effect on R : S . Accounting for these sources of variation is an important challenge for modelling (Franklin et al ., 2012).